Modelling for Climate Adaptation in Urban Drain Design with Orifice Flow Restrictor - Mah, Yau Seng; Merry Tang, Shi Ting; Rosmina, Ahmad Bustami; Wong, Yoke Seng; Nurhayati, Nurhayati; Frederik Josep, Putuhena (Semarak Ilmu Publishing, 2024)
Due to the increasing stormwater runoff in urban areas, stormwater infrastructure requires modification to address the flash flooding issues. Occurrences of floodwater overflowing the urban drain have urged drainage engineers to re-look its design. Conventionally, the urban drain is designed to free flow following the provided drain slope. This paper is challenging the old design by introducing orifices into the drain. The lesser-known stormwater characteristics restricted by orifices in open drains were investigated. In this case, twenty-four units of terrace houses were selected as the study area with special attention to the 170 m front drain with a dimension of 0.5 m x 0.55 m. The drain was inserted with one to three orifices of 0.45 m diameter separating the drain into one or more compartments. Three scenarios were formulated, namely S1 with one orifice plate at 170 m, S2 with two orifice plates at 86 and 170 m, and S3 with three orifices at 50, 110 and 170 m, from the starting point. Storm Water Management Model version 5.0 (SWMM5) was utilized to simulate and represent the unique characteristics of the three scenarios subjected to a 5-minute, 10-year average recurrent interval design storm. The analysis found that S1 had similar patterns with the existing condition and therefore, was insignificant. However, S2 and S3 demonstrated improved regulation of flow and water level along the drain. Between the two scenarios, S3 repeatedly displayed the most stable patterns, for example, S3 had a tight range of water levels between 0.30-0.34 m (compared to existing condition with fluctuating water levels between 0.32-0.50 m) and a tight range of flows between 0.01-0.08 m3/s (compared to existing condition with wider range of flows between 0.01-0.18 m3/s). The flows in S3 were reduced by half by introducing these series of orifices. These results point to an important finding that orifices were not worsening flood flushing in open drain but capable to regulate the flow and water level better than existing condition without any orifice. The capability of orifices to lower water levels allowing more spaces within the drain channel to accommodate climate-induced floodwater.